ROLE OF THE JUDGE IN CREATING JUSTICE AS AN INSTRUMENT OF SOCIAL CHANGE - MUH YUSUF; ICHSAN YASIN LIMPO; DEASY MAULIANA; ANDI BAU MALLARANGENG; MAKKAH HM (Universitas Bengkulu, 2016)
Abstract The roles of the judges in creating justice has been social phenomenon in society. Public response arises not only because it is so principal but also because the people want and expect that judges at all levels of the courts are qualified and have high integrity and social sensitivity so that it can resolve the problems in the legal field. This paper attempts to unravel the main duties of the judges solving the cases. It concludes in order to meet the demands of justice, the paradigm, mindset and behavior of judges that have tended to weaken and humiliate the position and dignity of the judiciary need to be changed and developed. To realize the existence of the role of judges is determined by the performance, professionalism, idealism and adequate infrastructure to support the efforts of both internal and external approach